A High-Performance Electrocatalyst for Oxygen Evolution Reaction: LiCo0.8Fe0.2O2 - Zhu, Y.; Zhou, W.; Chen, Y.; Yu, J.; Liu, M.; Shao, Zongping (2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Layered LiCo0.8Fe0.2O2 demonstrates dramatically enhanced oxygen evolution reaction (OER) activity and durability in an alkaline solution over LiCoO2 and other reported state-of-the-art catalysts, including benchmark IrO2. This superior performance is attributed to Fe-doping-induced synergistic effects.